Israel : Report on the Observance of Standards and Codes-Data Module, Response by the Authorities, Detailed Assessments Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2006)
This Report on the Observance of Standards and Codes-Data Module provides an assessment of Israel's macroeconomic statistics against the Special Data Dissemination Standard complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework, July 2003. The assessment reveals that Israel's macroeconomic statistics are of generally high quality and are broadly adequate to conduct effective surveillance. However, some shortcomings may impede the accurate and timely analysis of economic and financial developments and the formulation of appropriate policy.